Perspectivas acerca de la particiapación comunitaria de las mujeres del barrio "Los Pinos" enfocada a la vida cotidiana - Merizalde Chicaiza, Andrea Estefania (2016)
This investigation project will approach the thematic of community involvement focused on women's daily life in “Los Pinos” neighborhood, for this, it´s necessary to give a brief description of the territory and population, as well as the processes that have been led by the community. The present research has been approached with a field work with the duration of one year and three months, in which, was necessary the students inclusion and their work in different topics based on the community needs. For the research was necessary the application of IAP methodology, the use of focus groups and the field diaries as an important part of the activities that allowed the abstraction of the collected information registered in sightings and field works and participation. This research allows us understand in a better way, how women without being attached to an institution or establishment, they can generate participation either in their community or individually in different areas of development. For this investigation project have been used different tools that have generated approaches to different positions and conceptions of participation and a deeper understanding of reality attached to the women of “Los Pinos” neighborhood and their process of struggle and defend of their territory .